EFFECTIVENESS OF BASIC TRAINING FOR CIVIL SERVANT CANDIDATES (CPNS) USING THE KIRPETRICK LEVEL 3 MODEL (ATTITUDE AND BEHAVIOR) AND THE CONTINUATION OF PARTICIPANTS' ACTUALIZATION AFTER PARTICIPATING IN THE TRAINING IN THE WORK AREA OF THE RIAU ISLANDS L - Isdawati; Bambang Satriawan; Sri Yanti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to determine the effectiveness of the Kirpatrick Model Level 3 Civil Servant Candidate Training (behavioral attitudes) after Alumni complete the Training, supporting and inhibiting factors on the impact of training after Alumni complete the Training and to determine the sustainability of actualization after alumni complete the training. The research method used is quantitative descriptive. The instrument used as a data collection tool is in the form of in-depth interviews with 4 direct superiors, 8 co-workers and 8 training alumni. The results of this study indicate that the effectiveness of the training can be measured successfully through changes in attitudes, knowledge, and skills of participants as seen from their behavior in the workplace, this is reinforced by the results of interviews with direct superiors. The effectiveness of the Kirpatrick Model Level 3 Civil Servant Candidate Training (behavioral attitudes) after Alumni complete the Training, from the results of interviews with direct superiors of training participants who stated that CPNS Latsar participants were able to innovate in increasing work productivity, doing work according to work standards and being responsible. Related to understanding the supporting and inhibiting factors that influence the impact of training after alumni complete the training program, from the results of interviews with direct superiors of training participants who stated that support from direct superiors, co-workers, and the work environment played a very significant role in helping alumni of basic CPNS training implement training objectives, Basic PNS values, and develop technical skills according to their formation and position. Related to the sustainability of the actualization process of Prospective Civil Servants after alumni complete the training, the sustainability of the actualization program prepared by alumni of the Training varies, depending on the relevance of the program to the main tasks and functions of alumni in their new positions, as well as the support received from superiors and co-workers.